Acute Respiratory Distress Syndrome in Lemierre’s Syndrome - Paul N. Hein; Maida V. Soghikian; Munveer S. Bhangoo (Case Reports in Critical Care, 2014)
Lemierre’s syndrome is an infectious disease defined by the presence of septic thrombophlebitis with associated embolic phenomenon, most commonly to the lungs. Here we present two cases from a single institution of acute respiratory distress syndrome (ARDS) developing as a result of Lemierre’s syndrome in previously healthy young adult men. ARDS can occur as a consequence of pulmonary septic emboli and sepsis, both of which are well-described consequences of Lemierre’s syndrome. We describe important diagnostic and management considerations in the care of patients with hypoxemic respiratory failure and Lemierre’s syndrome. Essential components of management include prompt antibiotic therapy, lung-protective ventilation strategies, and supportive care.